School Principal Role In Handling Online Learning Issues During Covid-19 Pandemic - Gede Ari Utama; I Gusti Ketut Arya Sunu (International Journal of Educational Management and Innovation, 2022)
The school principal took a significant role in running the education process at school. The role of a school principal has become more complex during the Covid-19 pandemic. This study aimed to identify the school principals' roles in handling issues at school that the Covid-19 Pandemic caused. Specifically, this study identified the issues faced by students, parents, and teachers in the online learning process during the Covid-19 pandemic and how the school principal handled those issues. This study followed a literature review approach. The study data were collected from the research articles from indexed national and international journals and were analyzed qualitatively using the interactive data analysis model. The study results showed that students, parents, and teachers faced various problems in the online learning process. Those problems include infrastructure, time, financial, digital literacy, and psychological issues. Considering those problems, the school principals took a significant role in bridging students' and parents' demands with the issues faced by the teachers. The school principals took several strategies to solve the problems. The novel thing that this study offers is that the previous studies mostly viewed online learning issues from a specific point of view. However, this study tried to view those issues comprehensively and link those issues to the principal school roles. The researchers did that to get the bigger picture of the issues. Thus, the study results can be a basis for further studies that aim to improve the quality of online learning.